Less is more: The hormetic effect of titanium dioxide nanoparticles on plants - Trela-Makowej, Agnieszka; Orzechowska, Aleksandra; Szymańska, Renata (The Science of the total environment, 2024)
Titanium dioxide nanoparticles have attracted considerable attention due to their extensive applications; however, their multifaceted influence on plant physiology and the broader environment remains a complex subject. This review systematically synthesizes recent studies on the hormetic effects of TiO2 nanoparticles on plants - a phenomenon characterized by dual dose-response behavior that impacts various plant functions. It provides crucial insights into the molecular mechanisms underlying these hormetic effects, encompassing their effects on photosynthesis, oxidative stress response and gene regulation. The significance of this article consists in its emphasis on the necessity to establish clear regulatory frameworks and promote international collaboration to standardize the responsible adoption of nano-TiO2 technology within the agricultural sector. The findings are presented with the intention of stimulating interdisciplinary research and serving as an inspiration for further exploration and investigation within this vital and continually evolving field.Titanium dioxide nanoparticles have attracted considerable attention due to their extensive applications; however, their multifaceted influence on plant physiology and the broader environment remains a complex subject. This review systematically synthesizes recent studies on the hormetic effects of TiO2 nanoparticles on plants - a phenomenon characterized by dual dose-response behavior that impacts various plant functions. It provides crucial insights into the molecular mechanisms underlying these hormetic effects, encompassing their effects on photosynthesis, oxidative stress response and gene regulation. The significance of this article consists in its emphasis on the necessity to establish clear regulatory frameworks and promote international collaboration to standardize the responsible adoption of nano-TiO2 technology within the agricultural sector. The findings are presented with the intention of stimulating interdisciplinary research and serving as an inspiration for further exploration and investigation within this vital and continually evolving field.